Models in Software Engineering Workshops and Symposia at MODELS 2008, Toulouse, France, September 28 - October 3, 2008. Reports and Revised Selected Papers - Chaudron, Michel R. V. (Programming and Software Engineering,, 2009)
This book constitutes a collection of the best papers selected from the 12 workshops and 3 tutorials held in conjunction with MODELS 2008, the 11th International Conference on Model Driven Engineering Languages and Systems, in Toulouse, France, September 28 - October 3, 2008. The contributions are organized within the volume according to the workshops at which they were presented: Model Based Architecting and Construction of Embedded Systems (ACES-MB); Challenges in Model Driven Software Engineering (CHAMDE); Empirical Studies of Model Driven Engineering (ESMDA); Models@runtime; Model Co-evolution and Consistency Management (MCCM); Model-Driven Web Engineering (MDWE); Modeling Security (MODSEC); Model-Based Design of Trustworthy Health Information Systems (MOTHIS); Non-functional System Properties in Domain Specific Modeling Languages (NFPin DSML); OCL Tools: From Implementation to Evaluation and Comparison (OCL); Quality in Modeling (QIM); and Transforming and Weaving Ontologies and Model Driven Engineering (TWOMDE). Each section includes a summary of the workshop. The last three sections contain selected papers from the Doctoral Symposium, the Educational Symposium and the Research Project Symposium, respectively.